The prognostic relevance of HER2-positivity gain in metastatic breast cancer in the ChangeHER trial - Laura Pizzuti (Nature Portfolio, 2021)
Abstract In metastatic breast cancer (mBC), the change of human epidermal growth factor receptor 2 (HER2) status between primary and metastatic lesions is widely recognized, however clinical implications are unknown. Our study address the question if relevant differences exist between subjects who preserve the HER2 status and those who gain the HER2 positivity when relapsed. Data of patients affected by HER2-positive mBC, treated with pertuzumab and/or trastuzumab-emtansine (T-DM1) in a real-world setting at 45 Italian cancer centers were retrospectively collected and analyzed. From 2003 to 2017, 491 HER2‐positive mBC patients were included. Of these, 102 (20.7%) had been initially diagnosed as HER2-negative early BC. Estrogen and/or progesterone receptor were more expressed in patients with HER2-discordance compared to patients with HER2-concordant status (p < 0.0001 and p = 0.006, respectively). HER2-discordant tumors were characterized also by a lower rate of brain metastases (p = 0.01) and a longer disease free interval (p < 0.0001). Median overall survival was longer, although not statistically significant, in the subgroup of patients with HER2-discordant cancer with respect to patients with HER2-concordant status (140 vs 78 months, p = 0.07). Our findings suggest that patients with HER2-positive mBC with discordant HER2 status in early BC may have different clinical, biological and prognostic behavior compared to HER2-concordant patients.